Essentials of micro- and nanofluidics : with applications to the biological and chemical sciences - Conlisk, A. Terrence, 1950- (Cambridge : Cambridge University Press, 2013)
'This book introduces students to the basic physical principles to analyze fluid flow in micro and nano-size devices. This is the first book that unifies the thermal sciences with electrostatics and electrokinetics and colloid science; electrochemistry; and molecular biology. The author discusses key concepts and principles, such as the essentials of viscous flows, an introduction to electrochemistry, heat and mass transfer phenomena, elements of molecular and cell biology, and much more. This textbook presents state-of-the-art analytical and computational approaches to problems in all of these areas, especially electrokinetic flows, and gives examples of the use of these disciplines to design devices used for rapid molecular analysis, biochemical sensing, drug delivery, DNA analysis, the design of an artificial kidney, and other transport phenomena. This textbook includes exercise problems, modern examples of the applications of these sciences, and a solutions manual available to qualified instructors'--Provided by publisher.
Introduction and overview -- Preparatory concepts -- The governing equations for an electrically conducting fluid -- The essentials of viscous flow -- Heat and mass transfer phenomena in channels and tubes -- Introduction to electrostatics -- Elements of electrochemistry and the electrical double layer -- Elements of molecular and cell biology -- Electrokinetic phenomena -- Essential numerical methods -- Molecular simulations -- Applications.
Includes bibliographical references and index.
Keywords: Thermodynamics; Microfluidics; Nanofluids; Microelectromechanical systems; Nanostructures -- therapeutic use